Three new species and new distributional data for five rare species of Aphelinus (Hymenoptera: Aphelinidae) from China - Chen, Ye; Li, Cheng-De (Zootaxa, 2016)
Eight species of Aphelinus Dalman (Hymenoptera, Aphelinidae) from China are reviewed. Three species, A. pseudonepalensis sp. nov., A. truncaticlavus sp. nov. and A. maculigaster sp. nov. are newly described, four species, A. meghalayanus Hayat, A. huberi Hayat, A. sharpae Hayat, and A. maculatus Yasnosh are reported as new to China, and A. asychis Walker is newly reported from Tibet, China. A key to the Chinese species of Aphelinus based on females is given.